#TITLE_ALTERNATIVE# - BHAGASKARA (NIM : 15111034) ; Pembimbing : Prof. Dr. Ir. Hasanuddin Z.Abidin, M.Sc. : Dr. Irw, BHIMA
Related study of biomass is useful to show the wide variety of chemical biophysical processes, such as the condition of tree growth, and predict the impact that occurs on the ecosystem as a result of deforestation. Future Crop Trees (FCTs) is trees of current and potentially commercial timber species with adequate form and apparent growth potential. They also has ≥ 20cm diameter at breast height. This study aimed to estimate the biomass in the three categories of the tree stand density (infrequent, medium, and tight) with area sample of 0.04 hectares. One method of calculating the biomass is non-destructive sampling method with modeling of biomass into an allometric equation that convert volume into biomass by using Terrestrial Laser Scanner (TLS). Steps being taken in this research that are, literature study, determine the sample area and tree sampling, data acquisition, data processing, calculate stem commercial volume of trees then converted the volume into biomass, and validate the measurement results of TLS by comparing the results of measurements using a tape measure and distometer. Data processing includes the process of registration, filtering, meshing, and computation of biomass. The results of this research is biomass estimated value for each sample areas on three levels density of tree stands, where the sample trees are future crop trees. The measurement results using TLS can be declared valid due to differences in the size of the TLS results with the results of the measuring tape and distometer at 0.1 cm-1.4 cm. Estimated time of data collection TLS is 48 hours 10 minutes for nine sample plots with a three categoies tree stand density in Taman Hutan Raya Ir. H. Juanda, Bandung.